Next-Generation Bio-Composites: Alkali-Treated Borassus Husk Fiber for Structural and Thermal Efficiency - Md Atiqur Rahman; Mamadou Ndiaye; Bartosz Weclawski; Peter Farrell (Journal of Natural Fibers, 2025)
Natural fibers from renewable resources provide a sustainable alternative to synthetic reinforcements. This study examines the thermal and mechanical properties of Borassus husk fiber/epoxy composites, fabricated using untreated and alkali-treated fibers through the hand layup process. Fibers were treated with sodium hydroxide (NaOH) for 0.25–2 hours, and their thermal and thermo-mechanical properties were analyzed through thermogravimetric analysis (TGA) according to ASTM E2550, and dynamic mechanical analysis (DMA) was conducted adhering ASTM D5418–01 followed by scanning electron microscopy (SEM) analysis. Alkali treatment significantly enhanced thermal stability, as indicated by increased char content (11.5%) and higher integral process decomposition temperature (IPDT) values, with the 0.75-hour treated fiber/epoxy achieving the highest value (580°C). The composites exhibited superior mechanical stiffness and energy dissipation compared to neat epoxy (NE) and other bio-fiber composites. The glass transition temperature (Tg) increased significantly for 0.5TBHFE (94.6°C). Additionally, storage modulus and tanδ improved, with 0.5TBHFE offering the best stiffness–damping balance. A 34% reduction in total mass loss clearly indicates improved thermal stability, which is further supported by SEM images showing enhanced fiber–matrix interlocking. These findings highlight alkali-treated Borassus husk fiber composites can be promising structural materials for aerospace and automotive applications, contributing to eco-friendly and sustainable development.